INTERACTION OF NUTRIENT COMPOSITION, TEMPERATURE AND MOISTURE CONTENT OF BEAN SEEDS TO BRUCHID INFESTATION - Gbarage, Burabari M.; Uzakah, Richard P.; Nwanze, Judith A. C.; Zakka, Usman (FUDMA JOURNAL OF SCIENCES, 2024)
Baseline information for determining the role of nutrient composition, temperature and moisture content on the biological activities of bean weevils in storage was determined. The study was conducted using different temperature sources of black or white muslin clothing two moisture levels of 12±1% and 15±1% and a solarization periods of 48 hours, 72 hours and 96 hours. Disinfested cowpea seeds were infested with 4 pairs of pristine adult C. maculatus in each treatment combination and allowed to mate and oviposit. C. maculatus had no egg laid 24 hours, at 48 hours significantly high eggs were laid on cowpea seeds covered with white muslin cloths and exposed to 48 hours solarization. Percentage mortality on cowpea seeds covered with black and white muslin cloths and exposed to different hours of solarization showed that 100% mortality in cowpea seeds covered with black muslin cloth and exposed to 72 and 92 hours solarization. There was significant decrease in egg mortality in the control experiment. Solarization and use of black muslin cloth polypropylene sheet may serve as grain protectant when utilized effectively in suppressing bionomics of C. maculatus on cowpea seeds during storage.
Keywords: Solarization; Moisture content; Nutrient composition; Bionomics; Callosobruchus maculatus; Temperature